Efektivitas Terapi Penghambat Pompa Proton pada Anak dengan Otitis Media Kronik: Sebuah Laporan Kasus Berbasis Bukti - Joanna Erin Hanrahan; Nabilla Calista; Sabda Ardiantara; Ratna Dwi Restuti; Nina Irawati; Elvie Zulka Kautzia Rachmawati (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2023)
Introduction: In Indonesia, 82% of children with otitis media have experienced chronic otitis media (COM). COM has a high recurrency rate and is multifactorial, one of which is caused by acid reflux. Proton pump inhibitor (PPI) therapy has been used to treat acid reflux and gives excellent result. Purpose: Reporting one case of a child with COM and laryngopharyngeal reflux (LPR) who received PPI therapy. An evidence-based literature review was done to evaluate the effectiveness of PPI therapy in patient with COM and LPR.Methods: Literature searching was done through 3 databases. Critical appraisal based on the Oxford Center for Evidence Based Medicine Checklists 2011.Results: After we sorted out duplications and screened articles according to our inclusion and exclusion criteria, we retrieved one article. This article is valid and applicable, yet PPI therapy did not give significant clinical improvement because of some reasons.Conclusion: From the literature review, PPI therapy on patient with COM did not give significant clinical improvement such as to stop middle ear discharge, yet in our case, PPI therapy could produce a clinical improvement and in line with previous experimental studies. Therefore, PPI therapy could still be considered given in children with COM.